2011
DOI: 10.1007/s12664-011-0090-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of lipoic acid on methotrexate induced intestinal damage in rabbit model

Abstract: Methotrexate (MTX), a folate antagonist agent, is mainly used in treatment of malignant tumors and auto immune diseases and affects not only tumor cells, but also gastrointestinal mucosa. The present study was undertaken to determine whether lipoic acid (LA) could ameliorate methotrexate-induced oxidative intestine injury in rabbits. Twenty-one rabbits were randomly assigned into three groups: Group 1 (control group), Group 2 (received 20 mg/kg MTX), Group 3 (received MTX plus LA 75 mg/kg orally). On the 6th d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…This is due to increase in the cell death and decrease in the cell number. (8,9) The loss of architecture, inflammatory infiltration, disarrangements of acini ,vacuolation in the acinar cells of the minor salivary glands in the buccal mucosa, floor of the mouth is in agreement of the other studies which show that methotrexate induces loss of architecture, with disarrangements and marked swelling of the acini. (4) These marked changes in the minor salivary glands of oral mucosa suggests suppression and or disruption of protein synthesis of abnormal protein this can lead to formation of cytolysosome, some may be an evidence of the distinctive process called shrinkage necrosis ,this process has been described as apoptosis in a number of tissues and the apoptotic bodies which are found in small numbers in normal tissues and greatly increased in tissues which have been subjected to chemotherapy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is due to increase in the cell death and decrease in the cell number. (8,9) The loss of architecture, inflammatory infiltration, disarrangements of acini ,vacuolation in the acinar cells of the minor salivary glands in the buccal mucosa, floor of the mouth is in agreement of the other studies which show that methotrexate induces loss of architecture, with disarrangements and marked swelling of the acini. (4) These marked changes in the minor salivary glands of oral mucosa suggests suppression and or disruption of protein synthesis of abnormal protein this can lead to formation of cytolysosome, some may be an evidence of the distinctive process called shrinkage necrosis ,this process has been described as apoptosis in a number of tissues and the apoptotic bodies which are found in small numbers in normal tissues and greatly increased in tissues which have been subjected to chemotherapy.…”
Section: Discussionsupporting
confidence: 89%
“…Being a high affinity inhibitor of dihydrofolate reductase, methotrexate is a pro-oxidant compound that causes depletion of the dihydrofolate pool and directly affects the synthesis of thymidilate ,suppressing DNA synthesis .Therefore methotrexate affects not only tumor cells but also rapidly dividing cells such as gastrointestinal mucosa ,where it inhibits epithelial proliferation and induce apoptosis. (8,15,16) Recently, it has demonstrated that methotrexate causes significant reduction in the antioxidant enzymes levels, sensitizing the cells to reactive oxygen species (ROS). (17) The decrease in the weight of the animals in group II and Group III after treatment is mostly due to the loss of appetite due to the anti cancer therapy (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rabbits in group 2 (hypercholesterolemia plus quince treatment) drank and tolerated the decoction (100 ml/each). At the end of the experimental study (12 th week), the animals were sacrificed with an anesthetic overdose of ketamine plus acepromazine (Somi et al, 2011). Thereafter, the left testis was immediately resected, then washed with 0.9% NaCl, cut into 5 × 5 mm pieces and fixed in 10% neutral buffered formaldehyde.…”
Section: Methodsmentioning
confidence: 99%